Outcomes of catheter ablation of ventricular tachycardia in non-ischemic idiopathic dilated cardiomyopathy: A systematic review and meta-analysis - Ammar, Ahmed; Sharief, Mohamed; Abouelmagd, Khaled; Riad, Omar; Ibrahim, Mokhtar (Frontiers in Cardiovascular Medicine, 2022)
Objective: To perform a systematic review and meta-analysis of available trials regarding the outcomes of VT ablation in patients with NIDCM. Methods: A comprehensive database search of large four electronic databases, including PubMed, Cochrane, Scopus, and Institute for Scientific Information network meta-analysis, identified five studies enrolling 666 patients for patients with IDCM underwent CA for VT. The short-term outcomes assessed included procedural success, VT non-inducibility and procedural complications, whereas the long-term outcomes assessed included VT recurrence, heart transplantation, antiarrhythmic drugs (AAD) use after ablation and death. Results: A total of 5 observational studies reported outcomes in 666 patients with NIDCM undergoing VT catheter ablation. The complete procedural success was moderately high; 65.5% of the patients (95% CI 0.402- 0.857, p < 0.001) and the procedural complications occurred in 5.8% of the patients (95% CI 0.040-0.076, P = 0.685). During a follow up period of 12 to 45 months, there were VT recurrence in 34.2% of the patients (95% CI 0.301-0.465, p < 0.080), death in 20.2% of the patients (95% CI 0.059-0.283, p < 0.017) and heart transplantation in 12.9% of the patients (95% CI -0.026-0.245, P < 0.012). Conclusions: VT catheter ablation is effective and safe approach for management of patients with NIDCM with the epicardial approach to be considered as initial strategy. A multicentre randomized trial is crucial to look at the short- and long-term outcomes of VT ablation in NIDCM especially with the advances in mapping and ablation techniques and predictors of success.